2020
DOI: 10.1039/d0ra03144e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of tricyclic carbohydrate–benzene hybrids as selective inhibitors of galectin-1 and galectin-8 N-terminal domains

Abstract: Fused tricyclic carbohydrate–benzene hybrids carrying substituents at C10 and/or C11 were designed, synthesized and evaluated as inhibitors for galectin-1 and the N-terminal domain of galectin-8.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The popularity of this deiodosilylation approach with iodine monochloride to access other important, high‐value organic molecules including access to tricyclic carbohydrate‐benzene hybrids [10b] or alternatively towards Hagfeldt donor organic dyes [10c] has also recently been reported last year.…”
Section: Halogenation Of Arenes/alkenes/alkynes Using Iodine Monochloridementioning
confidence: 98%
“…The popularity of this deiodosilylation approach with iodine monochloride to access other important, high‐value organic molecules including access to tricyclic carbohydrate‐benzene hybrids [10b] or alternatively towards Hagfeldt donor organic dyes [10c] has also recently been reported last year.…”
Section: Halogenation Of Arenes/alkenes/alkynes Using Iodine Monochloridementioning
confidence: 98%
“…The discovery of a selective tricyclic galactalbenzene hybrid 3 has been described, which has an affinity of 180 μM for galectin-8N. [23] However, this compound is only twofold selective over galectin-1. Another reported galectin-8N ligand is galactomalonate 4, with a micromolar affinity for galectin-8N but no reported affinities for other galectins.…”
Section: Introductionmentioning
confidence: 99%
“…Of particular note is a recently reported tricyclic galactose-benzene hybrid 2 ( K d = 180 μM) which has about 2-fold selectivity over galectin-1 and a high 23-fold selectivity over galectin-3 ( Figure 1 ). 21 Published docking analyses of compound 2 in complex with galectin-8N suggested that the endocyclic double bond at the junction between the 3,4-dihydropyran ring and the adjacent phenyl ring of 2 lies within 3.5 Å to the electropositive side chain guanidinium ion of Arg45. 21 This distance would allow for an interaction between the double bond and Arg45.…”
mentioning
confidence: 99%
“… 21 Published docking analyses of compound 2 in complex with galectin-8N suggested that the endocyclic double bond at the junction between the 3,4-dihydropyran ring and the adjacent phenyl ring of 2 lies within 3.5 Å to the electropositive side chain guanidinium ion of Arg45. 21 This distance would allow for an interaction between the double bond and Arg45. Furthermore, the phenyl moieties of compound 2 were solvent-exposed and not in contact with galectin-8N amino acid side chains.…”
mentioning
confidence: 99%
See 1 more Smart Citation